Gross Anatomy, Morphometric and Micrometrical Studies of the Caecal Tonsil in Siruvidai Chicken of Tamil Nadu - P. Sridevi; Sabiha Hayath Basha; S. Usha Kumary; N. Pazhanivel; P. Veeramani; J. Violet Beaulah; Geetha Ramesh (The Indian Veterinary Journal, 2025)
The study aimed to investigate the gross morphological and micrometricage-related changes in the caecal tonsil of Siruvidai, a native chicken breed from Tamil Nadu. The tissue samples from six birds of each age were collected from day-old, 4thweek, 8thweek, 12thweek, 18thweek, 24th week and 52ndweeks respectively. Both male and female Siruvidai chickens were included in the study. Age-related morphological changes present in the caecal tonsil were observed and recorded. The topography of the caecal tonsil across all age groups was found similar, with slight variations in morphology. In the day-old and 4th week, the caecal tonsils were relatively underdeveloped, as tiny projections but from 12thweek onwards, they had become more clearly visible and more distinct and defined peanut size as the birds matured. This maturation was marked by an increase in the number and size of lymphoid follicles, enhancing the bird’s ability to mount an effective immune response. Statistical analysis of both morphometry and micrometrical data showed that caecal tonsil reached to their maximum size by 18thweek of age and gradually decreased during 24thand 52ndweek of age, which may be correlated with the depletion of the lymphoid tissue as age advanced. The caecal tonsil reached its peak activity by the 18th week of age in Siruvidai Chicken breed.